Alpha-1 antitrypsin gene polymorphism in Chronic Obstructive Pulmonary Disease (COPD) - Denden, Sabri (Sociedade Brasileira de Genética, 2010)
Alpha-1-antitrypsin (AAT) plays an important role in the pathogenesis of emphysema, the pathological lesion underlying the majority of the manifestations of Chronic Obstructive Pulmonary Disease (COPD). In this study we tested the hypothesis that common AAT polymorphisms influence the risk of developing COPDs. We investigated PiM1 (Ala213Val), PiM2 (Arg101His), PiM3 (Glu376Asp), PiS (Glu264Val) and PiZ (Glu342Lys) SERPINA1 alleles in 100 COPD patients and 200 healthy controls. No significant differences were observed in allele frequencies between COPD patients and controls, neither did haplotype analysis show significant differences between the two groups. A cross-sectional study revealed no significant relationship between common SERPINA1 polymorphisms (PiM1, PiM2, PiM3) and the emphysematous type of COPD. In addition, FEV(1) annual decline, determined during a two-year follow up period, revealed no difference among carriers of the tested polymorphisms.